The effect of eggshell powder on concrete brich performance as partial replacement of cement - Mohamad Hazmi, Marinamarican (2015)
Concrete is one of the materials that is widely used in construction all around the world. This material is widely used because it has several benefits such as, more durable, energy-efficient, low maintenance, affordability, fire-resistance, excellent thermal mass and also versatility. This study describes investigation into use of poultry waste in concrete development by incorporating with eggshell powder. Different eggshell powder concrete brick were developed by replacing 5-20% of eggshell powder for the cement in order to determine the optimum percentage and observe the strength of concrete brick to produce good cementations material for eggshell powder. The results indicated that eggshell powder can successfully be practice as partial replacement of cement in concrete brick production. The data collected show the cover strength development and durability properties. With respect to the results, at 5% replacement of eggshell the strength was higher than control concrete brick and indicates that 5% of eggshell replacement was an optimum content for maximum strength. Furthermore, the performance of eggshell powder concrete brick was comparable up to 10% eggshell powder replacement in terms of durability properties with control concrete brick.